2006
DOI: 10.1002/jcp.20823
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous expression of claudin‐5 induces barrier properties in cultured rat brain capillary endothelial cells

Abstract: Claudins are thought to be major components of tight junctions (TJs), and claudin-5 and -12 are localized at TJs of the blood-brain barrier (BBB). Claudin-5-deficient mice exhibit size-selective (<800 Da) opening of the BBB. The purpose of this study was to clarify the expression levels of claudin-5 and -12 in rat brain capillary endothelial cells, and to examine the ability of claudin-5 to form TJs in cultured rat brain capillary endothelial cells (TR-BBB). Expression of claudin-5 mRNA in rat brain capillary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
126
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(135 citation statements)
references
References 21 publications
(35 reference statements)
8
126
0
Order By: Relevance
“…Although CLN-3, CLN-5, and CLN-12 are all expressed by BMVECs (4), compelling evidence implicates CLN-5 as primarily responsible for determining the high trans-endothelial resistance of BBB tight junctions (5,6). Within the brain, CLN-5 is restricted to endothelium and expression of its mRNA within this compartment is more than 750 times that of CLN-12 (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CLN-3, CLN-5, and CLN-12 are all expressed by BMVECs (4), compelling evidence implicates CLN-5 as primarily responsible for determining the high trans-endothelial resistance of BBB tight junctions (5,6). Within the brain, CLN-5 is restricted to endothelium and expression of its mRNA within this compartment is more than 750 times that of CLN-12 (5).…”
Section: Discussionmentioning
confidence: 99%
“…Claudins act as the main determinants of tight junction properties (3), and BMVECs predominantly express CLN-5, with smaller amounts of CLN-3 and CLN-12 (4). Transfection studies show that CLN-5 plays a key role in the appearance of BBB properties (5), and CLN-5 -/-mice display selective BBB opening (6). OCLN is also a tight junction strand component, and contributes to junction properties and regulates permeability (7), but strands form normally in OCLN-deficient cells (8), and OCLN -/-mice display a complex phenotype (9).…”
mentioning
confidence: 99%
“…The tight junction of BBB consists of transmembrane molecules, Occludin, Claudin, and junctional adhesion proteins that are linked to the actin cytoskeleton through cytoplasmic accessory proteins including Zo-1, Zo-2, and Zo-3 (5,6). Occludin and Claudin were identified particularly as critical proteins of BBB integrity (37)(38)(39)(40)(41). In this study we have shown A, tumor initiating cells were prepared from MB-MB231 and 231BrM using CD24, CD44, and ESA markers as described under "Experimental Procedures."…”
Section: Discussionmentioning
confidence: 99%
“…It resides within cerebral and pulmonary endothelial cells at the cell-cell border, but not in epithelial cells, including astrocyte end-feet (Nitta et al, 2003). Claudin-5 is predominantly expressed in brain capillaries, and appears to have a key role in the barrier to egress of small molecules by brain capillary endothelial cells (Morita et al, 1999;Ohtsuki et al, 2007). In one study, the normalized claudin-5 mRNA level in the rat brain capillary fraction was 35.6-fold greater than that in the brain (Ohtsuki et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…After 7 days hypoxia, retinal vascular claudin-5 expression in the rat decreases and extravasation of an injected 534 Da tracer increases compared with normoxic retina (Koto et al, 2007). Complementary work in culture has demonstrated that after transfection of claudin-5 gene into rat brain capillary endothelial cells, the inulin paracellular permeability coefficient of the endothelial cell monolayer decreases (Ohtsuki et al, 2007). Separately, increased claudin-5 protein expression paralleled an increase in the transendothelial electrical resistance (TEER) of bEnd.3 monolayers during the growth phase.…”
Section: Introductionmentioning
confidence: 99%